Characteristics and genesis of light oil in Tabei Area, Tarim Basin, Northwestern China - Wang, Yang; Zhang, Shaonan; Xie, Honglei; Wang, Qi; Tian, Jinqiang (Frontiers in Earth Science, 2023)
Light oil is a high-quality crude oil. The formation and chemical composition of light oil is a matter of great concern to petroleum geologists. Yakela Field and Shunbei Field which are located in Yakela and Shunbei regions respectively are the two main light oil fields in the Tabei uplift of the Tarim Basin. In order to identify the causative mechanism of light oils in these two fields, seventeen crude oil samples were selected and analyzed by gas chromatography for saturated and gas chromatography-mass spectrometry for saturated and aromatic hydrocarbons. The molecular geochemical characteristics show that the light oils in the two fields are sourced from similar marine source rocks deposited under the weak oxidative and reductive environments. The maturity of crude oil in the Shunbei Field is higher than that in the Yakela Field. Simulation results of hydrocarbon generation history of source rocks in two fields showed that the formation mechanism of the two light oils is different. The light oil in the Yakela Field is directly generated by the source rock in the late oil-generating window. The crude oil in the Shunbei Field is formed by the deep burial and maturation of the crude oil generated in the early stage of the source rock.